Analisis Pengaruh Solvabilitas dan Struktur Kepemilikan Terhadap Nilai Perusahaan (Studi pada Perusahaan Pertambangan di Bursa Efek Indonesia Tahun 2011-2013) - Marjono jono; Ullan Alvian (Jurnal Ekonomi Integra, 2014)
In this research, we investigated impact of the solvability ratio and the ownership to the corporate value. We use causality research by using multiple regression analysis method to solve the hypothesis. As conclusion, only the ownership has the significant impact to the corporate value, while the Solvability ratios as the independent variable didn’t have significant impact to the corporate value. In simultaneity, both independent variable have positive influence to the corporate value as the dependent variable.